Percutaneous Discectomy—Continuous Irrigation and Drainage for Tuberculous Lumbar Spondylitis: A Report of Two Cases - Sei Shibuya; Satoshi Komatsubara; Tetsuji Yamamoto; Nobuo Arima; Yoshiaki Kanda; Shiro Oka (Case Reports in Medicine)
Percutaneous curettage and continuous irrigation were performed for definitive diagnosis and treatment of tuberculous (TB) lumbar spondylitis. Under local anaesthesia, affected lumbar discs were curetted using a procedure of percutaneous nucleotomy, and in-tube and the out-tube were placed for continuous irrigation. The period of continuous irrigation was 12–16 days. Mycobacterium tuberculosis was demonstrated in case 1 by culture and PCR, whereas histology showed tuberculous lesion with caseous necrosis in both cases. Postoperative MRI showed markedly reduced abscesses after 3 months in both cases. The signal intensity in vertebral bodies was improved. In Case 2, CT observations showed remodeling over time in the vertebral body cavities. This method is advantageous in that although minimally invasive, it achieves identification of pathogenic bacteria and treatment simultaneously. This surgical procedure is expected to prove effective for both TB and pyogenic spondylitis.